FACTORS INFLUENCING RETENTION OF REMOTE EMPLOYEES AT PLACEMENT INTERNATIONAL - Purba, Wynona Sheehan; Kumar, Suresh (President University, 2024)
This study aims to explore and analyse the factors influencing the retention of remote employees, focusing on the role of a supportive remote work environment, organizational commitment, person-organization fit, and work fulfilment. The research seeks to understand how these variables interact and contribute to long-term employee retention within a remote work setting. By examining these relationships, the study provides valuable insights into the dynamics of remote work environments and their influence on organizational stability and employee satisfaction. A quantitative research design was employed, with data collected through an online survey distributed via Google Forms to remote employees at Placement International. Data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart PLS 3. The findings reveal that a supportive remote work environment positively influences organizational commitment, person-organization fit, and work fulfilment. Additionally, organizational commitment and work fulfilment are shown to positively impact remote employee retention, while person-organization fit does not directly influence retention. This research offers actionable insights for companies employing remote workforces, highlighting the importance of fostering a supportive work environment to enhance employee commitment and fulfilment, which are critical for improving retention rates. These findings can guide HR policies and remote work strategies to ensure long-term workforce stability. The study contributes to understanding how remote work environments can be optimized to improve the quality of life for employees by focusing on factors that enhance their work experience and overall well-being, which is especially relevant in the growing shift toward flexible work arrangements. This research is pioneering in its investigation of remote employee retention, incorporating the variables of supportive work environment, organizational commitment, person-organization fit, and work fulfilment. Furthermore, it is the first to study these relationships within the context of Placement International, offering a novel contribution to both academic literature and business practice.